Improving Indonesia's Plantation Data Quality: Coffee, Sugar and Cocoa - Kadir Ruslan; Octavia Rizky Prasetyo (Center for Indonesian Policy Studies (CIPS), 2021)
Until now, the plantation sub-sector is still faced with the structural issue of a poor plantation data collection system. The data are still collected using a lengthy and stage-by-stage business process, carried out manually, causing an administrative product compilation method that is vulnerable to error and the subjectivity of the data collection officers. This policy paper analyzes the importance of plantation data collection system improvement, especially for several strategic plantation commodities, such as coffee, cocoa, and sugarcane. In the short and medium term, improvements to data collection systems can focus on modernizing business processes and improving methodologies. Meanwhile, in the long run, a data collection method that is based on objective measurements, such as the remote sensing method using satellite images should be developed to improve the quality of data on the planted areas.
Keywords: 330; Plantation productivity; coffee plantations; cocoa plantations; sugar cane plantations; agriculture; plantation crops; cips policy paper; cips plantation data; kadir ruslan plantations; kadir ruslan; plantation data; improving plantation data; indonesian plantation; agriculture policy; indonesian agriculture data; indonesian plantation data; plantation policy indonesia; food commodity indonesia.